Total Synthesis of Quebrachamine through Macrolactamization (Eur. J. Org. Chem. 15/2014). Issue 15 (May 2014) - Hsu, Shih‐Wen; Cheng, Hsiu‐Yi; Huang, An‐Chi; Ho, Tse‐Lok; Hou, Duen‐Ren
Abstract : The cover picture shows the spectacular scenery of the Guoxing Interchange, located in Nantou, Taiwan. The loop‐like structure, lifted by the high piers up to 70 meters above the ground, equivalent to 23 stories, is the most high‐rise interchange system of the freeways in Taiwan. In the microscopic world, the nine‐membered, macrocycle of quebrachamine was constructed by direct lactamization. The conformationally restricted cis ‐2‐alkenylindole is the key component for the total synthesis, which was achieved in ten linear steps with a 9 % total yield. Details are discussed in the article by D.‐R. Hou et al. onp. 3109 ff. Photography by Aaron Fan.